Pediatric dental radiography: safety, techniques and diagnostic applications - Al Domyati, Roaa Mohammad; Zagzoog, Ghaida Mazen; Khalid Obaid, Abdulrahman; Al Shehri, Rawad Homoud; Al Blowi, Randah Hamza; Shibatalhamd, Khalid Yousef; Bahkali, Rahmah Mohammed; Munthery, Ahmed Ali; Demyati, Mawadh Abdulrahman; Alshehri, Shahad Amer; Hakami, May Mohammed (International Journal Of Community Medicine And Public Health, 2023)
Children, with their higher cellular metabolism, longer lifespans, and smaller bodies, require specific adjustments in X-ray settings. The increased mitotic cell activity in children, coupled with their longer life expectancy, raises concerns about the potential long-term effects of radiation exposure, such as tumor development or cancer-related deaths. Therefore, radiographs should be prescribed based on individual patient needs, balancing the necessity for diagnostic clarity with the risks of radiation. Radiographs play a vital role in the diagnosis of traumatic dental injuries, as they can reveal injuries that may not be apparent through clinical examination alone. In pediatric dentistry, radiography is essential for diagnosing dental caries, monitoring growth, and identifying developmental or pathological conditions. They are invaluable in treatment planning and assessing dentofacial structures. However, the decision to use radiography should follow a comprehensive assessment, considering each child’s medical, dental, as well as the clinical background, as well as environmental factors. Special techniques and considerations are necessary for infants, young children, individuals with disabilities, as well as those with gag reflexes.